Antiviral Compounds Analysis in Ethanol and Methanol Extracts of Jamblang Fruit (Syzygium cumini) Using the GCMS Method - Purba, Febi Anjaini; Diningrat, Diky Setya; Sari, Ayu Nirmala; Harahap, Novita Sari; -, Kusdianti (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2021)
Jamblang fruit (Syzygium cumini) is a plat that has been scientifically researched to have medicinal properties.This study aims to determine the content of bioactive compounds contained in the petiole by Gas Chromathography Mass Spectrophotometer (GCMS) method. The study used gas chromatographic tools and mass spectra which were evaluated using MASSLAB program. The data obtained from the GCMS machine is then analyzed using the NCBI database pubchem software (https://pubchem.ncbi.nlm.nih.gov/). The result showed that there were 61 phytochemical compounds in jamblang root ethanol extracts and 33 compounds in jambang fruit methanol extracts. Then 4 of them being the same compound, located in each of the extract. Of the total bioactive compounds, there are 5 phytochemical compounds that are useful as antiviral with details, 2 from the extract ethanol of jamblang and 2 from the extract methanol of jamblang. The results of this study can be used as the foundation in the development program of the potential utilization of bioassemblance of jamblang plants. In further research it is necessary to analyze the other parts of the plant and make comparisons to complete the available database.